Histone acetyltransferase 1 is required for DNA replication fork function and stability - Agudelo Garcia, Paula A. (J Biol Chem, 2020)
The replisome is a protein complex on the DNA replication fork and functions in a dynamic environment at the intersection of parental and nascent chromatin. Parental nucleosomes are disrupted in front of the replication fork. The daughter DNA duplexes are packaged with an equal amount of parental and newly synthesized histones in the wake of the replication fork through the activity of the replication-coupled chromatin assembly pathway. Histone acetyltransferase 1 (HAT1) is responsible for the cytosolic diacetylation of newly synthesized histone H4 on lysines 5 and 12, which accompanies replication-coupled chromatin assembly. Here, using proximity ligation assay-based chromatin assembly assays and DNA fiber analysis, we analyzed the role of murine HAT1 in replication-coupled chromatin assembly. We demonstrate that HAT1 physically associates with chromatin near DNA replication sites. We found that the association of HAT1 with newly replicated DNA is transient, but can be stabilized by replication fork stalling. The association of HAT1 with nascent chromatin may be functionally relevant, as HAT1 loss decreased replication fork progression and increased replication fork stalling. Moreover, in the absence of HAT1, stalled replication forks were unstable, and newly synthesized DNA became susceptible to MRE11-dependent degradation. These results suggest that HAT1 links replication fork function to the proper processing and assembly of newly synthesized histones.